PERAN LEMBAGA PENDIDIKAN MUHAMMADIYAH DALAM PENDIDIKAN SAINS TERINTEGRASI AGAMA DAN ETIKA - Arifah Khusnuryani (Tajdidukasi: Jurnal Penelitian dan Kajian Pendidikan Islam, 2010)
Science and technology have been integrated into almost every aspect of human life. The development of science-technology raise a dilemma, in one hand it gives many benefits that can improve the quality of human life, but on the other hand it also has some disadvantages related to the technology itself and the ethical aspect of the development of science-technology. Therefore, we need an education about wisdom in developing science-technology through religion education or other disciplines which deliver ethics or values. Muhammadiyah is one of Islamic social-society board which has some institution of education, from early stage until higher education. Those institutions of education in Muhammadiyah have an important and strategic role in delivering education of science-technology which is integrated with religion and ethics, and vice versa. Ethics education, especially bioethics, usually is delivered for medical students. However, there is a thought that this ethics education should be delivered to early stage until higher education. Therefore, Majelis Pendidikan Dasar dan Menengah and Majelis Pendidikan Tinggi Muhammadiyah has important role in formulating and developing the education of science-technology which is integrated with religion and ethics. Then the education institution of Muhammadiyah can produce some scientists who competence in their disciplines which is based with religion and ethics values. Key Words: Science-Technology, Religion, Ethics and Muhammadiyah